Measuring Medication Adherence in Pediatric Cancer: An Approach to Validation. (16th May 2016) - Rohan, Jennifer M.; Fukuda, Tsuyoshi; Alderfer, Melissa A.; Wetherington Donewar, Crista; Ewing, Linda; Katz, Ernest R.; Muriel, Anna C.; Vinks, Alexander A.; Drotar, Dennis
Abstract : Objective This study described the prospective relationship between pharmacological and behavioral measures of 6-mercaptopurine (6MP) medication adherence in a multisite cohort of pediatric patients diagnosed with cancer ( N = 139). Methods Pharmacological measures (i.e., metabolite concentrations) assessed 6MP intake. Behavioral measures (e.g., electronic monitoring) described adherence patterns over time. Results Three metabolite profiles were identified across 15 months: one group demonstrated low levels of both metabolites (40.8%) consistent with nonadherence and/or suboptimal therapy; two other groups demonstrated metabolite clusters indicative of adequate adherence (59.2%). Those patients whose metabolite profile demonstrated low levels of both metabolites had consistently lower behavioral adherence rates. Conclusions To our knowledge, this was the first study to prospectively validate a pharmacological measure of medication adherence with a behavioral adherence measure in a relatively large sample of pediatric patients with cancer. Using multiple methods of adherence measurement could inform clinical care and target patients in need of intervention.